MATERNAL ANTIBODY PERSISTENCE AGAINST THE CLASSICAL SWINE FEVER VIRUS IN PIGLETS BORN FROM VACCINATED SOWS IN FARMS WITH DIFFERENT VACCINATION STRATEGIES - Portilla J., Katherine (2009)
In the study was evaluated the persistence of maternal antibodies levels against the Classical Swine Fever virus (CSFV) in piglets born from vaccinated sows from two farms (A and B) with different vaccination strategies against CSFV. In farm A sows were vaccinated at 90 days of gestation and in farm B at 18 - 21 days postpartum. Serum samples were collected from piglets of both farms, at first (n=15), third (n=15), fifth (n=15) and seventh (n=15) weeks of age, and from 15 sows from each farm A for detection of antibodies against CSFV by the indirect ELISA test. All piglets had maternal antibodies against CSFV at first week of age, persisting in most of them to the seventh week of age. Significant differences between farms were found (p<0.05) on levels of maternal antibodies in piglets at first and third week of age. Also, higher variability on antibody levels was observed n piglets and sows in farm A. The results suggest that the level and persistence of the maternal antibodies in piglets depend of vaccination strategies against PPC virus.